Determination of inorganic cations in dry milk samples deposited on a microdialysis probe by capillary electrophoresis - Tůma, Petr (Food chemistry, 2025)
A tubular microdialysis probe is made from polysulfone hollow fibre for human haemodialysis, which has an inner diameter of 200 μm and a thickness of 20 μm. Milk is deposited to the outer surface of the hollow fibre and allowed to dry to form a dry sample. The tubular probe is then connected to the syringe pump and microdialysis of the dry sample into 0.5 mol/L HCl as acceptor is performed. 2.5 μL of microdialysate is obtained and analyzed for inorganic cations by capillary electrophoresis with contactless conductivity detection. Baseline separation of NH4+, K+, Ca2+, Na+, Mg2+, Li+ is achieved in 5.5 mol/L acetic acid as background electrolyte using a fused silica capillary with inner diameter of 25 μm and length of 31.5 cm. The reproducibility of dry sample microdialysis including CE analysis for peak area ranges from 2.4 to 3.9 % after normalization to Li+ as internal standard.
Keywords: Dry samples; skot; Cations; mléko; Conductivity detection; Animals; Cattle; elektroforéza kapilární; Capillary electrophoresis; mikrodialýza; kationty; Electrophoresis, Capillary; Milk; Microdialysis; zvířata; Miniaturization